Autism in adulthood: improving the future - Howlin, Patricia (Henry Stewart Talks, 2021)
Adult outcomes for individuals with autism, Positive and negative aspects of autism in adulthood, Predictors of outcome in adulthood, Interventions for adults with autism, Future research needs